How, why and when are delayed (back-up) antibiotic prescriptions used in primary care? A realist review integrating concepts of uncertainty in healthcare - Monsey Mcleod; Anne Campbell; Benedict Hayhoe; Aleksandra J. Borek; Sarah Tonkin-Crine; Michael V. Moore; Christopher C. Butler; A. Sarah Walker; Alison Holmes; Geoff Wong; on behalf of the STEP-UP study team (BMC, 2024)
Abstract Background Antimicrobial resistance is a global patient safety priority and inappropriate antimicrobial use is a key contributing factor. Evidence have shown that delayed (back-up) antibiotic prescriptions (DP) are an effective and safe strategy for reducing unnecessary antibiotic consumption but its use is controversial. Methods We conducted a realist review to ask why, how, and in what contexts general practitioners (GPs) use DP. We searched five electronic databases for relevant articles and included DP-related data from interviews with healthcare professionals in a related study. Data were analysed using a realist theory-driven approach - theorising which context(s) influenced (mechanisms) resultant outcome(s) (context-mechanism-outcome-configurations: CMOCs). Results Data were included from 76 articles and 41 interviews to develop a program theory comprising nine key and 56 related CMOCs. These explain the reasons for GPs' tolerance of risk to different uncertainties and how these may interact with GPs' work environment, self-efficacy and perceived patient concordance to make using DP as a safety-net or social tool more or less likely, at a given time-point. For example, when a GP uses clinical scores or diagnostic tests: a clearly high or low score/test result may mitigate scientific uncertainty and lead to an immediate or no antibiotic decision; an intermediary result may provoke hermeneutic (interpretation-related) uncertainty and lead to DP becoming preferred and used as a safety net. Our program theory explains how DP can be used to mitigate some uncertainties but also provoke or exacerbate others. Conclusion This review explains how, why and in what contexts GPs are more or less likely to use DP, as well as various uncertainties GPs face which DP may mitigate or provoke. We recommend that efforts to plan and implement interventions to optimise antibiotic prescribing in primary care consider these uncertainties and the contexts when DP may be (dis)preferred over other interventions to reduce antibiotic prescribing. We also recommend the following and have included example activities for: (i) reducing demand for immediate antibiotics; (ii) framing DP as an 'active' prescribing option; (iii) documenting the decision-making process around DP; and (iv) facilitating social and system support.